The Subjective Estimation of the Body Dimensions - Strzałko, Jan; Lewicki, Piotr K T.; Kaszycka, Katarzyna (Anthropological Review, 2022)
The subjective estimation of the body dimensions was investigated on 1372 school-children of both sexes aged 11-18 years. The analysis of the consistency of estimations (selfestimations and mutual estimations) with the real values of the particular traits (stature, body weight and hand muscle strength) permitted to draw conclusions referring to the perception of the morphological diversity, of man.